KARAKTERISTIK FISIK DAN KIMIA LINGKUNGAN PERAIRAN LAUT UDANG BARONG (Panilurus, sp) UNTUK POTENSI USAHA BUDIDAYA SECARA BERKELANJUTAN - Rustam Rustam; Hartinah Hartinah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
Barong shrimp or lobster (Panilurus sp) is one of the fishery commodities that has high economic value. However, until now barong shrimp is still widely done with the effort of fishing activities only. The frequency of high capture so that the resources of barong shrimp in this marine ecosystem are increasingly decreasing and there can even be excess capture (over fishing) and damage marine resources as a place to live barong shrimp. The purpose of this study is (1) Analysis of the physical and chemical characteristics of the marine waters of barong shrimp, (2) Determining the location / land suitable for the business of shrimp farming. The research method is to use field survey methods by collecting primary and secondary data. Primary data includes the physical and chemical parameters of marine waters. Secondary data collected from related reports and documents include, potential coastal and marine resources, climatological characteristics, batimethri, substrate types, and related policies. The results of the analysis of the area of the suitability value of the location of the waters for the development of Barong shrimp sea cultivation in the waters of Barrang Caddi Island were obtained 3.31 ha and did not match 0.60 ha. The result of the physical and chemical parameters of the waters is; (a) The físika parameter consists of: depth of 4.10 m – 20.5 m, brightness of 6.00 m - 8.20 m, current speed of 0.14 m / second - 0.39 m / second (b). Chemical Parameters consist of water temperature ranging from 27.0 ºC - 29.00 ºC, salinity of waters by 31.50 ppt - 35.20 ppt, (e). pH of 7.32 - 8.50. The results of the evaluation of the value of the suitability of the waters for the development of Barong shrimp sea cultivation in the waters of Barrang Caddi Island covering an area of 3.31 Ha. Keywords;